Rekognisi Tradisi Khitan Perempuan dalam Hukum Konstitusi (Harmonisasi Hukum Adat dan Perlindungan Hak Asasi Manusia di Indonesia) - Alyza Lailyah Putri (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The teachings and practices of FGM/C in syariat agama Islam are considered part of the right to worship and the right to practice one’s own religion, including how to believe in and carry out religious commandments. However, the practice is no longer relevant to present-day needs and health studies. The findings indicate that regulatory improvements are needed as a strong legal umbrella applicable throughout Indonesia, despite the special authority granted to certain regions. Such regulations can take the form of Presidential Decrees (Keputusan Presiden or Kepres), Government Regulations (Peraturan Pemerintah or PP), and Ministry of Health Regulations (Peraturan Menteri Kesehatan or Permenkes). Recognition of FGM/C through symbolic ceremonies could be considered as an alternative, such as small incisions on the clitoral hood without removing any part, cleaning the female genitalia (similar to the hair-cutting ritual in aqiqah), and the abolition or elimination of FGM/C practices.